PROFESSIONAL TRAINING OF ECONOMIC INDUSTRY SPECIALISTS IN THE CONTEXT OF GLOBAL SUSTAINABLE DEVELOPMENT - Sysoev Alexey (Освітологія, 2021)
The article substantiates the urgent need to modernize the training of future professionals, in particular economists, in the context of global sustainable development; the substantiation is made on the basis of the analysis of problems of global sustainable development. The scientific analysis of the problem shows that the authors often focus on environmental and resource-economic issues, sometimes on demographic factors, while covering the problem. Among the factors influencing global sustainable development, the author includes: the activities of the Institute of Education, the implementation of its leading preventive function — training professionals to comply with the principles of sustainable development in their professional activities. Education is a significant potential for sustainable development of society. Its role is to predict, form and develop throughout life the professional competence of future professionals, to develop an energy-efficient style of professional activity. To a large extent, this applies to the training of professionals for the economic sector, as most of the global environmental problems that hamper sustainable development have economic roots. Under such conditions, there is a need to modernize the training of specialists, in particular economists, in the context of the tasks of global sustainable development. It is concluded that solving the problems of global sustainable development in education should include: development of ecological culture of pupils and students, greening of educational courses in secondary and higher education institutions, involving students in the system of postgraduate education; investigation of the latest technologies and methods of prevention and prevention of ecological catastrophes; introduction of new directions of professional training of specialists; introduction of specialists’ training in circular economy (green economy, closed cycle economy) in Ukraine.